2022
DOI: 10.3390/antiox11040742
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Bioactive Compounds in Food: Critical Review of Issues and Prospects

Abstract: This review paper gives an insight into the effective delivery mechanisms for health-promoting substances and highlights the challenges of using antioxidants and bioactives in foods. The selection criteria for choosing bioactives and their extraction in bioavailable form with their adequate incorporation techniques and delivery mechanisms are covered. Moreover, an overview of existing methods for determination of bioactivity is given. The importance of scientifically evaluating the effects of foods or food com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 156 publications
0
16
0
1
Order By: Relevance
“…In the process of normal cellular metabolism, free radicals and reactive species, such as reactive oxygen species (ROS), are created continuously in the human body. Endogenous enzymatic and nonenzymatic defense systems quickly remove free radicals and reactive species; however, under certain conditions, such as drug use, inflammation, air pollution, smoking, and irradiation, endogenous antioxidant systems can be overwhelmed, resulting in oxidative stress, which can cause aging, cancer, and atherosclerosis [ 70 , 71 ]. Although numerous studies have revealed that hydrolyzed peptides and proteins reduce enzymatic and nonenzymatic oxidation by eliminating free radicals and chelating metal ions, the exact mechanism by which mushroom peptides exert antioxidant properties is still not entirely understood.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…In the process of normal cellular metabolism, free radicals and reactive species, such as reactive oxygen species (ROS), are created continuously in the human body. Endogenous enzymatic and nonenzymatic defense systems quickly remove free radicals and reactive species; however, under certain conditions, such as drug use, inflammation, air pollution, smoking, and irradiation, endogenous antioxidant systems can be overwhelmed, resulting in oxidative stress, which can cause aging, cancer, and atherosclerosis [ 70 , 71 ]. Although numerous studies have revealed that hydrolyzed peptides and proteins reduce enzymatic and nonenzymatic oxidation by eliminating free radicals and chelating metal ions, the exact mechanism by which mushroom peptides exert antioxidant properties is still not entirely understood.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Currently, the focus in industry and research is not only to find new antioxidants to further fulfil these legal conditions but also to replace as many synthetic food additives [ 109 ] as possible with ones based on natural antioxidants [ 110 ] from vegetable sources, and special attention is given to the ones of marine origin [ 111 ] for lipid systems. From the biochemical point of view, it is known that antioxidants can be for lipid systems or for hydrophilic systems [ 82 , 87 , 110 ], the ones for lipid systems are widely used in the food industry [ 109 ], and some examples are given below [ 86 , 109 ].…”
Section: Antioxidants As Food Additivesmentioning
confidence: 99%
“…The plant-based diet has become the equivalent of many curative and prophylactic treatments [ 48 , 109 , 262 , 263 ]. The importance of the consumption of vegetables and fruits is explained by the beneficial intake of antioxidants as they are being active in numerous biological processes of the body at the cellular level [ 109 , 264 ].…”
Section: Natural Antioxidants and Their Benefitsmentioning
confidence: 99%
“…Ekstraksi merupakan proses penting untuk memperoleh senyawa bioaktif. Teknik ekstraksi yang semakin berkembang saat ini (Kurek et al 2022) berpengaruh pada status halal dari senyawa bioaktif. Persyaratan halal bahan mengikuti ekstrak tanaman level 1.…”
Section: Profil Kritis Halal Bahan Perisa Kelompok Senyawa Bioaktifunclassified